Navigating peace, conflict, and human security within the Switzerland-Slovakia sustainable energy framework under the 2060 Strategy - Sutiono, Pribadi; Salsabila, Ghina Aulia; Shenindita, Nadila Putri; Pradana, Muhammad Andhika (Privietlab, 2026)
. As the global community approaches the 2026 UN Summit of the Future, international structures governing resources and energy face a profound legitimacy crisis, requiring integrated systems to ensure human security. This study evaluates the alignment of Switzerland’s 2060 strategy with emerging global mandates for equitable governance, specifically examining the tension between Swiss diplomatic neutrality and the developmental imperatives of the UN’s pact for the future. Utilizing a comparative policy analysis framework, the research leverages OECD data, Swiss federal policy instruments, and the UN’s proposed governance breakthroughs to analyze the Swiss-Slovak Cooperation Programme as a primary case study. The analysis reveals a significant convergence gap between Switzerland’s rhetoric of inclusive transformation and its institutional application. In the Slovak context, Swiss support is frequently confined to technical niches such as vocational training and environmental protection while maintaining a detached stance toward broader economic convergence and regional energy equity. Findings indicate that current Swiss bilateral policy operates in a state of fragmentation that negates the multiplier effects intended by the UN Rescue Plan. This paper provides a strategic roadmap for reforming bilateral frameworks, ensuring that energy and resource-based contributions catalyze long-term economic stability and peacebuilding rather than merely funding projects.